Paper profits from value, size and momentum: Evidence from the Polish market - Adam Zaremba; Przemysław Konieczka (e-Finanse: Financial Internet Quarterly, 2015)
In this paper we investigate sources and characteristics of value, size and momentum profits on the Polish stock market. The research aims to broaden the academic knowledge in a few ways. First, we deliver fresh out-of-sample evidence on value, momentum, and size premiums. Second, we analyzemthe interdependences among the factors. Third, we investigate whether the factor premiums are present after accounting for liquidity constraints. Fourth, we check whether the factor premiums are robust to transaction costs. Our research is based on all the stocks listed on the WSE in years 2001-2013. We find, that the value, momentum, and size premiums are to some extent present on the Polish market. Furthermore, they strengthen each other, but they disappear after accounting for transaction costs and liquidity.
Keywords: G11; G12; G14; 330; value premium; size premium; momentum effect; cross-section of stock returns; liquidity; transaction costs; Warsaw Stock Exchange; WSE; Polish stock market